Supernumerary Axillary Breast. Case Presentation and Bibliography Review - Lidia Torres Aja; Tamara Ramírez Rodríguez; José Alberto Puerto Lorenzo (Revista Finlay)
Several disorders in the structure and morphology of the mammary gland have been described as a result of variations of its development regulating mechanism. It may be found anomalies in number, size, form and location. Among the most frequent congenital anomalies, regarding number, supernumerary breast and regarding location abnormal breast tissue. Both may be the basis for malignant tumors and in a higher frequency the abnormal breast tissue. The abnormal or ectopic breast tissue may present with different forms. It is presented a case of a 48 year old woman from health area 4 at the Cienfuegos municipality who had an abnormal breast tissue on the left axillary, with a secretory orifice from which milk is secreted during pregnancy. Due to the low frequency occurrence of this disease, the publication of this case is considered of scientific interest.